EARLY RESULTS OF OESOPHAGECTOMY FOR CARCINOMA OESOPHAGUS IN 1008 CASES - Bilal, Bilal A; Baseer, Baseer A; Ahmad, Ahmad M; Imran, Imran M; Abid, Abid M; Kalimullah, Kalimullah M (Journal of Ayub Medical College Abbottabad, 2010)
Objective: To determine the early results of 1008 oesophagectomies done for carcinoma oesophagus over a 9 years period. Methods: This observational descriptive study was conducted at Department of Cardiothoracic Surgery, Lady Reading Hospital, and Khyber Medical Centre Peshawar from June 2002 to June 2011. All patients had apart from routine investigations, Barium studies, Endoscopy and biopsy, CT thorax/upper abdomen with oral and I/V contrast and abdominal ultrasound. The operative approaches included left thoracolaparotomy with left neck anastomosis, transhiatal, left thoracolaparotomy with Roux en-Y, McKeown with right decortication, Ivor Lewis and left thoracolaparotomy with left decortication. All operations were done by one surgical team. The hospital records and operation reports of these patients were carefully analysed for demographic feature; operative approach and outcome. Results: Out of 1008 cases, 698 were males and 310 were females with a mean age of 51.6 years. The age range was 17-80 years. Out of 1008 cases 611 (60.61%) cases had lower one third tumours, 384 (38.09%) cases had middle one third tumours while 13 (1.28%) tumours were just below the thoracic inlet. Of the 611 lower …“ tumours stomach involvement was present in 271 (44.35%) cases. Adenocarcinoma was present in 516 (51.19%) cases, squamous cell carcinoma was present in 485 (48.11%), adenosquamous was 6 (0.59%) and carcinoma in situ was present in 1 case (0.09%). Morbidity was 63/1008 (6.25%), and comprised anastomotic leaks 15, aspiration pneumonia 13, wound infection 13, hoarseness 8, and strictures 14, 30-day mortality was 23/1008 (2.28%) and causes included aspiration pneumonia-respiratory failure (5), myocardial infarction (4), anastomotic leak (6), tracheal injury (2), and presumed pulmonary embolism (6). Conclusion: More than 1000 cases in 9 years is a very high oesophageal workload for malignancy. Morbidity of 6.25% and mortality of 2.28% shows that such major operations can be done safely in thoracic centres. Keywords: oesophagectomy, carcinoma oesophagus, outcome